Investigating Virtual Reality in Postsecondary Anatomy Education - Bernardo, Ashley A.; MacDougall, Joanna C. (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2026)
The use of virtual reality (VR) in education is rapidly increasing, and research supports its potential to enhance student understanding, motivation, and satisfaction. This study examined the perceived value, helpfulness, and limitations of VR in a first-year postsecondary anatomy course. The course included weekly labs with anatomical models and integrated VR sessions using head-mounted devices and the anatomy software application 3D Organon. Eleven students completed an anonymous survey and participated in a focus group. Participants rated both VR and traditional lab materials as somewhat or very helpful, reporting improvements in understanding (n = 9), enjoyment (n = 8), and motivation (n = 6). Focus group feedback highlighted VR’s ease of use and its ability to provide interactive three-dimensional views beyond what physical models or flashcards offer. Disinfection procedures and ease of use were identified as potential challenges; side effects were minimal and may have been mitigated by following usage guidelines. The course professor noted that VR fostered a barrier-free environment and increased student confidence and collaboration. These findings support VR as a valuable complementary tool in education.